Effect of low planting density on the spikelet number in 'Tachisuzuka', a rice (Oryza sativa L.) cultivar with a short panicle for whole crop silage use. (18th June 2013) - Matsushita, Kei; Iida, Shuichi; Ideta, Osamu; Ishii, Takuro; Fujimoto, Hiroshi; Watanabe, Hajime; Takahashi, Yoshihiko
Abstract: A promising new cultivar of rice ( Oryza sativa L.) 'Tachisuzuka' has been developed for silage use with improved feeding value due to a radical decrease in spikelets. However, 'Tachisuzuka' has the problem of inefficient seed production. We investigated the effect of planting density on the spikelet number in 'Tachisuzuka' to find out how seed yields of this cultivar can be increased by means of cultivation methods. 'Tachisuzuka' was cultivated at six different planting densities, in the range of 7.4 – 22.2 hills m −2 . Unlike in ordinary cultivars, there was a negative correlation between the spikelet number per unit area and hills per unit area. Moreover, the spikelet number increased by 67% under the low planting density. This result implies that the efficiency of seed production of 'Tachisuzuka' could be improved by low planting density through an increase in spikelet number per unit area.